Preocupările și interesele adolescenților în sfera creației literare - Drăghici, Elisaveta (Calitatea Vieții, 2016)
The study undertaken aims to show that teenagers are concerned about the literary activity and want to make a contribution, aspiring to be a writer. They are interested to master the techniques of writing and focus their behaviour toward development of creative and literary resources: they search for environments where recognized writers are present, exploring their world, they are concerned about the use of literary talents and willing to make writing a tool for personal development. communication and also to obtain recognition of their work. Teens have a great need for expression through writing and the confirmation of their creative capacity. Writing is strong concern for adolescents, it is an objective in planning for the future, whether it will be dedicated to writing or that it will be a secondary activity along with their profession. As a generation, teenagers feel the need to tell the world what they think and feel and want to bring changes considering writing as a way of action